2019
DOI: 10.1016/j.mex.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Two CRISPR/Cas9-mediated methods for targeting complex insertions, deletions, or replacements in mouse

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For the conditional Tgfbr1 inactivation approach we used three Tgfbr1 alleles, namely the Tgfbr1 null allele 37 and either Tgfbr1 flox , carrying LoxP sites flanking Exon 3 52 , or Tgfbr1 3 ex 3 -flox , containing a triplicated Exon 3 each surrounded by LoxP sites (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the conditional Tgfbr1 inactivation approach we used three Tgfbr1 alleles, namely the Tgfbr1 null allele 37 and either Tgfbr1 flox , carrying LoxP sites flanking Exon 3 52 , or Tgfbr1 3 ex 3 -flox , containing a triplicated Exon 3 each surrounded by LoxP sites (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generation of the Tgfbr1 Flox mouse lines was previously reported 48 . Tgfbr1 3ex3-flox resulted from the same experiments in which Tgfbr1 flox was generated, identified upon sequencing through the Tgfbr1 locus, which revealed that the exon 3 had been triplicated and the presence of LoxP sites in the introns between the triplicated exons and in those connecting them with exon 2 and exon 4.…”
Section: Methodsmentioning
confidence: 99%
“…For the conditional Tgfbr1 inactivation approach we used three Tgfbr1 alleles, namely the Tgfbr1 null allele 37 and either Tgfbr1 flox , carrying LoxP sites flanking Exon 3 48 , or Tgfbr1 3ex3-flox , containing a triplicated Exon 3 each surrounded by LoxP sites (supplementary Fig. 1).…”
Section: Generation Of Tgfbr1-cko Developmental Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This doesn't mean we can't use it for dsDNA. By targeting both dsDNA (DiNapoli et al, 2020[ 29 ]) and ssDNA (Bai et al, 2020[ 12 ]) templates in cells, experimental animals (Pineault et al, 2019[ 102 ]), plants (Mao et al, 2019[ 87 ]), model organisms (Bai et al, 2020[ 11 ]) and even humans (Ma et al, 2015[ 79 ]; Moon et al, 2019[ 91 ]), we can regulate insertions, deletions, replication, migration, transformation, copy number loss or gain (Anzalone et al, 2019[ 6 ]) with the CRISPR system. Different Cas enzymes are preferred according to the mechanisms by which they are effective in all these biological structures.…”
Section: Mechanisms Of Genome Editing Toolsmentioning
confidence: 99%